Elaboration of the pathological profile of schools in the urban area of Machala, exposed to pesticides used in banana crops - Santos Luna, Jovanny (2017)
This paper presents the results obtained in a study conducted in the period 2013-2014 to determine the pathological profile of a sample of 200 schoolchildren from two urban-marginal schools in Machala, El Oro province, Ecuador, aged between 4-12 years, exposed to contact with pesticides used in the fumigation of banana crops.Individual characteristics of the children analyzed, such as sex, nutritional status and social stratum, among others, were determined and studies of blood cytometry and plasma cholinesterase were performed.Laboratory tests were not conclusive for the diagnosis of chronic intoxication, which may be related to the type of pesticide used, the time of exposure and the absence of reference values for this age group differentiated by sex.The symptomatology determined in almost all children is related to muscarinic or parasympathetic symptoms that occur in pesticide poisonings.